RESOLUTION OF XII CONGRESS OF RUSSIAN CHILDREN'S INFECTIOLOGISTS «ESSENTIAL ISSUES OF INFECTIOUS PATHOLOGY AND VACCINATION», 11—13 th December 2013, Moscow - статья Редакционная (Детские инфекции (Москва))
.